Co-expression of BCL2 and C-MYC as a Potential Predictive Factor of Survival in Diffuse Large B Cell Lymphoma with Rituximab-Based Chemotherapy - Salimah, Kun; Hardianti, Mardiah Suci; Anggorowati, Nungki; Taroeno-Hariadi, Kartika Widayati (Asian Pacific Journal of Cancer Biology, 2026)
Objective: Diffuse Large B Cell Lymphoma (DLBCL) is a heterogeneous disease with varying aggressiveness and response to therapy. The co-expression of BCL2 and C-MYC has been reported to hold prognostic value for disease outcomes. This study aimed to determine the proportion of DLBCL patients with co-expression of BCL2 and C-MYC at Dr. Sardjito Hospital and evaluate its association with clinicopathological features and survival. Methods: This retrospective cohort study included 72 DLBCL patients treated with rituximab-based chemotherapy between January 2017 and December 2019. The co-expression of BCL2 and C-MYC was evaluated using immunohistochemistry. The Kaplan-Meier method was used along with the log-rank test to assess 5 years overall survival and to compare the two groups. Cox proportional hazards regression was applied to identify factors affecting survival. Result: The proportion of patients with BCL2 and C-MYC co-expression was 12.5% (9/72 patients). These patients exhibited a trend toward poorer survival compared to those without co-expression (median OS: 26 months [95% CI: 0.000–52.296] vs. 71 months [95% CI: 55.057–86.943]; p = 0.156). However, the co-expression of BCL2 and C-MYC did not demonstrate predictive value for 5-year survival in DLBCL patients receiving rituximab-based chemotherapy. Conclusion: DLBCL patients with BCL2 and C-MYC coexpression demonstrated a trend toward shorter survival compared to those without co-expression. However, this co-expression was not identified as an independent prognostic factor for 5-year survival in DLBCL patients treated with rituximab-based chemotherapy.